Hemolysis Compromises Nitric Oxide-Dependent Vasodilatory Responses in Patients Undergoing Major Cardiovascular Surgery - Hanssen, Sebastiaan J.; van de Poll, Marcel C.; Houben, Alfons J.; Windsant, Iris C. Vermeulen; Snoeijs, Maarten G.; Bekers, Otto; Buurman, Wim A.; Jacobs, Michael J. (The Thoracic and Cardiovascular Surgeon, 2012)
Background The hemolytic products cell-free oxyhemoglobin (FHb) and arginase-1 reduce nitric oxide (NO) bioavailability by scavenging NO and by degrading the NO precursor arginine to ornithine, respectively. In this study we evaluated the relevance of hemolysis to NO-dependent blood flow in patients undergoing cardiovascular surgery.Methods Plasma FHb, arginase-1, and amino acid concentrations were measured perioperatively. Forearm blood flow (FBF) responses to the intra-arterial administered NO-donor sodium nitroprusside (SNP) and the endothelium-dependent vasodilator acetylcholine (ACh) were measured by venous occlusion plethysmography.Results When peak values plasma FHb and arginase-1 were found, vascular dilatation to SNP, but not ACh, was significantly reduced compared with 1 day postoperatively, when FHb had returned to baseline levels (p < 0.05). Interestingly, plasma FHb concentration was inversely correlated to FBF responses to SNP (r −0.93, p < 0.001). In contrast, the increase in arginase-1 was not biologically relevant as the ratio of plasma arginine to ornithine remained constant.Conclusion We conclude that hemolysis with concomitant release of FHb during cardiovascular surgery is associated with impaired NO-dependent forearm blood flow.
Keywords: cardiopulmonary bypass; nitric oxide; vascular science (biochemistry pharmacology pathology)